Project-based learning model and self-efficacy: improving cognitive learning and sports massage skill - Gede Doddy Tisna MS; I Ketut Budaya Astra; I Gede Suwiwa (Physical Education Departement of University PGRI Jombang, 2025)
Current pupils have low achievement and poor massage learning skills. The purpose of the study was to ascertain how well Department of Physical Education students' cognitive learning accomplishment and sports massage abilities might be enhanced by the project-based learning model (PjBL) and self-efficacy. A post-test control group design was used in conjunction with a quasi-experimental design. There were 141 students in 6 classes in the Department of Physical Education. The samples for this study consisted of 4 groups (76 students), each of which had 19 students. The groups were formed based on self-efficacy and learning models. Multiple-choice tests were used to assess learning achievement, and a massage skills test was used to assess skills. The inferential statistical analysis of MANOVA was applied to the data analysis process. The findings indicated that the PjBL model and self-efficacy had a simultaneous and partial effect on improving cognitive learning achievement and sports massage skills; additionally, the PjBL had a greater impact on these outcomes than direct instruction; third, the high self-efficacy had a greater impact on these outcomes than the low self-efficacy; and finally, the interaction between the learning models (PjBL and direct instruction) with self-efficacy (high and low) had a significantly different effect on these outcomes. Therefore, the grouping of strong and low self-efficacy has varying effects on the learning model (PjBL and direct teaching) employed for cognitive learning achievement and sports massage abilities. In the Department of Physical Education, the PjBL model and self-efficacy are advised to enhance students' cognitive learning success and sports massage abilities.